Հումորը՝ որպես ազգային ինքնության արտացոլում Ն.Դումբաձեի վեպում - Ն. Մ. Բալայան (ՀՀ ԳԱԱ հրատ.)
В основе романа Нодара Думбадзе «Я, бабушка, Илико и Иларион» лежит национальный юмор. С помощью небольших историй, повествуемых главным героем, автор раскрывает типологические отличия национального характера. Некоторые персонажи романа Думбадзе наделены свойствами представителей животного мира, а животные в романе уподоблены людям. Nodar Dumbadze’s novel "Me, Grandma, Iliko and Ilarioni" is based on a humour reflecting the national identity. Through the story of the main character, the author reinstates national characteristics and folklore originated features. The characters of the novel, people and animals, are interrelated, yet substituent.
Keywords: Literature; Language and Literature